Epithelial immune activation and intracellular invasion by non-typeable Haemophilus influenzae - Brown, Mary A.; Morgan, Sophie B.; Donachie, Gillian E.; Horton, Katie L.; Pavord, Ian D.; Arancibia-Cárcamo, Carolina V.; Hinks, Timothy S. C. (Frontiers in Cellular and Infection Microbiology, 2023)
Type-2 low asthma affects 30-50% of people with severe asthma and includes a phenotype characterized by sputum neutrophilia and resistance to corticosteroids. Airways inflammation in type-2 low asthma or COPD is potentially driven by persistent bacterial colonization of the lower airways by bacteria such as non-encapsulated Haemophilus influenzae (NTHi). Although pathogenic in the lower airways, NTHi is a commensal of the upper airways. It is not known to what extent these strains can invade airway epithelial cells, persist intracellularly and activate epithelial cell production of proinflammatory cytokines, and how this differs between the upper and lower airways. We studied NTHi infection of primary human bronchial epithelial cells (PBECs), primary nasal epithelial cells (NECs) and epithelial cell lines from upper and lower airways. NTHi strains differed in propensity for intracellular and paracellular invasion. We found NTHi was internalized within PBECs at 6 h, but live intracellular infection did not persist at 24 h. Confocal microscopy and flow cytometry showed NTHi infected secretory, ciliated and basal PBECs. Infection of PBECs led to induction of CXCL8, interleukin (IL)-1β, IL-6 and TNF. The magnitude of cytokine induction was independent of the degree of intracellular invasion, either by differing strains or by cytochalasin D inhibition of endocytosis, with the exception of the inflammasome-induced mediator IL-1β. NTHi-induced activation of TLR2/4, NOD1/2 and NLR inflammasome pathways was significantly stronger in NECs than in PBECs. These data suggest that NTHi is internalized transiently by airway epithelial cells and has capacity to drive inflammation in airway epithelial cells.